A supervised machine learning approach to predict vulnerability to drug addiction - Faisal, Fahim; Shahriar, Arif; Mahmud, Sohan Uddin; Shuvo, Rakibul Alam (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.